Antibacterial Effect of Cold Aqueous Pomegranate Peel Extract Compared with Chlorhexidine Against Streptococcus mutans Isolated from Gingivitis and Dental Caries - Etab Abdul-Ameer AL-Ogla; Haneen Seed mohsin Al-Mosawei (Kerbala Journal of Nursing and Health Sciences., 2026)
Background: Streptococcus mutans is a major cariogenic bacterium implicated in dental plaque formation, gingivitis, and dental caries. Although chlorhexidine (CHX) is widely used as an antimicrobial mouthwash, its long-term use is associated with several undesirable side effects, prompting the search for effective natural alternatives. Aim: This study aimed to evaluate the antibacterial activity of a cold aqueous pomegranate peel extract (PPE) and to compare its efficacy with 0.2% chlorhexidine against Streptococcus mutans isolated from patients with gingivitis and dental caries. Methods: A total of 55 clinical isolates of Streptococcus mutans were obtained from patients attending dental clinics. Antibacterial activity was assessed using agar disk diffusion. Minimum inhibitory concentration (MIC), minimum bactericidal concentration (MBC), and time-kill assays were performed using standard broth microdilution methods. Results: PPE exhibited a larger mean inhibition zone than chlorhexidine (26.0 ± SD mm vs. 24.0 ± SD mm). The MIC and MBC values of PPE (0.78 mg/mL and 1.56 mg/mL, respectively) were lower than those of chlorhexidine (1.25 mg/mL and 2.50 mg/mL). Time-kill analysis demonstrated a rapid and sustained reduction in viable bacterial counts with PPE compared to chlorhexidine. Conclusion: The cold aqueous extract of pomegranate peel demonstrated significant in vitro antibacterial activity against S. mutans and showed greater efficacy than chlorhexidine in several parameters. These findings suggest that PPE may represent a promising natural candidate for further clinical evaluation in oral healthcare applications.